1990
DOI: 10.1073/pnas.87.24.9828
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations of nerve during cuff compression.

Abstract: Whether compression nerve injury is due to ischemia, direct mechanical injury, or both remains unsettled. To assess structural changes of nerve during compression, peroneal nerves of rats were compressed at various pressures for different times, and the structural alterations were stopped by simultaneous in situ and perfusion fixation. The structural changes observed during a few minutes of compression cannot be explained by ischemic injury because the pathologic alterations characteristic of ischemia take man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…It remains to be determined whether paranodal demyelination contributes to the conduction block caused by lysolecithin injections (Smith and Hall, 1980). Paranodal demyelination is also caused by wide variety of immune (Ballin and Thomas, 1969a,b;Allt, 1975;Bonnaud-Toulze and Raine, 1980), toxic (Allt, 1969;Jones and Cavanagh, 1983;Griffin et al, 1987), and mechanical (Lubinska, 1958;Ochoa, 1972;Foster et al, 1980;Dyck et al, 1990;Abe et al, 2002) agents. In spite of its potential importance, its only molecular attribute is that paranodal demyelination splits nodes into two heminodes of Na V channels (Dugandzija-Novakovic et al, 1995;Novakovic et al, 1996).…”
Section: Molecular Reorganization Accompanying Paranodal Demyelinationmentioning
confidence: 97%
“…It remains to be determined whether paranodal demyelination contributes to the conduction block caused by lysolecithin injections (Smith and Hall, 1980). Paranodal demyelination is also caused by wide variety of immune (Ballin and Thomas, 1969a,b;Allt, 1975;Bonnaud-Toulze and Raine, 1980), toxic (Allt, 1969;Jones and Cavanagh, 1983;Griffin et al, 1987), and mechanical (Lubinska, 1958;Ochoa, 1972;Foster et al, 1980;Dyck et al, 1990;Abe et al, 2002) agents. In spite of its potential importance, its only molecular attribute is that paranodal demyelination splits nodes into two heminodes of Na V channels (Dugandzija-Novakovic et al, 1995;Novakovic et al, 1996).…”
Section: Molecular Reorganization Accompanying Paranodal Demyelinationmentioning
confidence: 97%
“…Dyck et al 45 found that endoneurial fluid, axoplasm, and myelin were displaced away from regions of rat peroneal nerve that were acutely pressurized. At the site of compression, there was an increase in the distance between nodes of Ranvier and distortion of myelin lamellae.…”
Section: Evidence Of Peripheral Nerve Injury In Wmsdsmentioning
confidence: 99%
“…Axonal caliber is considered to be largely determined developmentally. A special role of neurofilaments in influencing caliber has been deduced from the observation that neurofilament density is relatively constant among axons of different calibers (Friede and Somarajski, 1970;Hoffman et al, 1984), although regional differences (Nixon and Logvinenko, 1986;Lasek, 1988;Price et al, 1990;Reles and Friede, I99 l), changes in axonal diseases (Parhad et al, 1987;Dyck et al, 1990) and alterations due to interrupted axon-target interactions (Hoffman et al, 1984) all indicate that neither neurofilament number nor density is fixed or immutable.…”
Section: Regional Modulation Of Neurofilament Organization By Myelinamentioning
confidence: 99%